Nexus requirements for taxation of non-residents' business income : a normative evaluation in the context of the global economy - Gadžo, Stjepan (Amsterdam, The Netherlands : IBFD, 2018)
This book contains a critical evaluation of the nexus requirements for the taxation of non-residents' business income enshrined in the current rules of international tax law and provides a proposal that is more aligned with international tax policy benchmarks.
3.2.1. An illustration: Taxation of non-residents' business income in Croatia -- 3.2.1.1. PE concept in the Croatian Profit Tax Act -- 3.2.1.2. Special rules on services income -- 3.2.1.3. Taxation of business income of non-resident individuals under the Income Tax Act -- 3.3. Model 2: Usage of the PE concept defined substantially different than in tax treaty models -- 3.3.1. An illustration: PE concept under German tax law -- 3.3.1.1. PE concept in the German Fiscal Code -- 3.3.1.2. Usage of "permanent representatives" by non-residents: Secondary nexus test
Originally presented as the author's thesis (doctoral--Sveučilište u Zagrebu, 2016).
Includes bibliographical references (page [339]-385).
Description based on print version record.
eBooks on EBSCOhost
Keywords: Income tax -- Law and legislation; Income tax -- Foreign income; Double taxation; Impôt sur le revenu -- Revenus étrangers.; Double imposition; Double taxation; Income tax -- Foreign income; Income tax -- Law and legislation